Aspen seedling establishment, survival, and growth following a high-severity wildfire - Kreider, Mark R.; Yocom, Larissa L. (Forest ecology and management, 2021)
•Widespread, prolific aspen seedling establishment occurred one year following fire.•Seedlings were more likely to occur at higher elevations and closer to seed sources.•Seedlings only established on burned soil, and preferred protected microsites.•Survival and growth of seedlings was reduced by competition with aspen suckers. Quaking aspen (Populus tremuloides) is an important component of western U.S. forests, however knowledge concerning processes of aspen seedling establishment, survival, and growth is limited and frequently anecdotal. Following a widespread post-fire establishment event in southern Utah, we explored spatial establishment patterns of >1000 aspen seedlings and tracked their survival and growth for two growing seasons. Specifically, we assessed the influence of landscape-level variables, microsite factors, and competition with suckers on aspen seedling establishment, survival, and growth. Aspen seedlings occurred across large areas of the 29,000 ha fire footprint, with an average plot density of 23,033 seedlings ha−1, and establishment more likely at higher elevations and closer to seed sources. Aspen seedlings preferentially established in concave microsites and were tightly associated with burned soil. A total of 33% of tagged seedlings remained alive after two growing seasons. Seedling persistence was strongly impacted by competition with co-occurring aspen suckers, with survival lower for aspen seedlings closer to nearby suckers and seedling growth reduced in plots with high sucker density. Given the long dispersal distances of aspen seeds and the ability of seeds to take advantage of initial post-disturbance conditions, sexual regeneration in aspen may represent an important pathway for maintaining forest resilience and associated ecosystem services, especially following fires with large patches of high burn severity.